Carbonate chemistry and coral reefs in the Pacific coast of Costa Rica - Sánchez Noguera, Celeste (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2019)
Coral reefs are important tropical ecosystems holding about 25% of the world marine biodiversity. Their tridimensional biogenic structures are built of calcium carbonate and they are threatened by global warming and ocean acidification. Current projections on the future development of coral reefs suffer among others from the scarcity of local observations, especially along the Costa Rican coast in the Eastern Tropical Pacific (ETP). The aim of this thesis was to investigate the carbonate chemistry in coastal waters and their effect on the reef development along this coast. It reveals a strong gradient from reefs influenced by upwelling in the north towards reefs affected by river discharges in the south. Due to this gradient we selected three study sites: Santa Elena in the north, Marino Ballena in the south and Matapalo between these two sites. Parameters required to determine the carbonate system (pH, pCO2, TA and DIC) including temperature, salinity and nutrients were measured during the dry and rainy season. Furthermore, the benthic composition was quantified by reef surveys and in situ studies were carried out to identify the effect of local environmental variables on reef organisms. Our results evidenced that coastal upwelling and metabolic reactions (photosynthesis and respiration) are the main drivers in the north (Santa Elena), whereas calcification and carbonate dissolution in addition to river discharges exert a strong control on the carbonate chemistry in the south (Marino Ballena). The dominant coral species in the south (Porites lobata and Pavona clavus) cope with enhanced suspended matter concentrations, a low salinity, and a low aragonite saturation state (Ωa). Reef-builders in the north (Pavona gigantea, Pavona clavus and Pocillopora sp.) are also tolerant to low Ωa but are adapted to low sea water temperatures and euthrophic conditions. However, enhanced nutrient inputs into reefs enhance productivity, which in turn favors the growth of larger and more effective benthic bioeroders. In addition ...